Cerebral strokes in children on intracorporeal ventricular assist devices: analysis of the EUROMACS Registry. (25th September 2017) - Schweiger, Martin; Miera, Oliver; de By, Theo M M H; Hübler, Michael; Berger, Felix; Özbaran, Mustafa; Loforte, Antonio; Seifert, Burkhardt; Gargiulo, Gaetano; Gummert, Jan; Mohacsi, Paul; ,
Abstract: OBJECTIVES: Little is known about cerebral strokes in paediatric patients supported by intracorporeal continuous-flow ventricular assist devices. METHODS: We retrospectively investigated patients younger than 19 years of age who were treated with an intracorporeal continuous-flow ventricular assist device in the European Registry for Patients with Mechanical Circulatory Support (EUROMACS) database. The patients were stratified by body surface area in Group 1 [<1.2 m 2 ( n = 13)] and Group 2 [≥1.2 m 2 ( n = 38)]. Cerebral strokes, both ischaemic and haemorrhagic, were studied. RESULTS: Of the 2941 patients with ventricular assist device (VAD) implants listed in the database, 124 (4%) patients were less than 19 years of age. Fifty-one of them (2%) were supported with a continuous-flow ventricular assist device. Group 1 (6 female and 7 male) had a mean age (±SD) of 9 ± 2.3 years compared with 15.6 ± 1.8 years in Group 2 (21 female and 17 male). Three (23%) patients died in Group 1 on VAD support, whereas 5 (13%) patients died in Group 2 ( P = 0.21; log-rank test). Seven (54%) patients with a VAD in Group 1 and 17 (45%) patients in Group 2 underwent transplantation ( P = 0.29); of these, 1 (8%) patient recovered (Group 1) with subsequent device explantation. The other patients, 2 in Group 1 and 16 in Group 2, were still on device support at the time of the analysis. There were no cerebral strokes in Group 1, but 4 cerebral strokes (11% of Group 2, 8% of a total of 51 patients in Groups 1 and 2 combined) occurred in Group 2 (3 patients died; P = 0.26; log-rank test). Taken together, the incidence of cerebral strokes in this paediatric cohort of patients with an intracorporeal VAD was 0.1 per patient-year. CONCLUSIONS: The incidence of cerebral strokes in children with intracorporeal VADs (0.1 per patient-year) seems to be low irrespective of the body surface area.